2016
DOI: 10.1155/2016/4760414
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Practical Issues That Are Relevant When Scaling Up hMSC Microcarrier Production Processes

Abstract: The potential of human mesenchymal stem cells (hMSCs) for allogeneic cell therapies has created a large amount of interest. However, this presupposes the availability of efficient scale-up procedures. Promising results have been reported for stirred bioreactors that operate with microcarriers. Recent publications focusing on microcarrier-based stirred bioreactors have demonstrated the successful use of Computational Fluid Dynamics (CFD) and suspension criteria (N S1u, N S1) for rapidly scaling up hMSC expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 41 publications
2
69
0
Order By: Relevance
“…It has been shown that successively transferring a small proportion of near-confluent MCs (10-25%) into a new vessel loaded with fresh MCs leads to a decrease of lag phase and an increase of the overall yield (35,38). Even if using MCs can lead to the formation of cell-loaded MCs aggregates that can inhibit proliferation, adding fresh MCs in combination with adapted agitation have been shown to reduce MCs aggregation (41)(42)(43). Although different techniques, such as intermittent stirring, have been implemented to enhance cell transfer and limit clumping of MCs, no robust method for SCs has been reported so far.…”
Section: Scalability Of Sc Culture Through the Use Of Mcsmentioning
confidence: 99%
“…It has been shown that successively transferring a small proportion of near-confluent MCs (10-25%) into a new vessel loaded with fresh MCs leads to a decrease of lag phase and an increase of the overall yield (35,38). Even if using MCs can lead to the formation of cell-loaded MCs aggregates that can inhibit proliferation, adding fresh MCs in combination with adapted agitation have been shown to reduce MCs aggregation (41)(42)(43). Although different techniques, such as intermittent stirring, have been implemented to enhance cell transfer and limit clumping of MCs, no robust method for SCs has been reported so far.…”
Section: Scalability Of Sc Culture Through the Use Of Mcsmentioning
confidence: 99%
“…In the present study, we attempt to investigate the influence of hydrodynamic conditions on aggregation kinetics of hMSC on a rocking platform. Rocking cultures characterized by intermittent wave motion are not only used in laboratory stem cell culture but also in large scale production such as in wave motion bioreactors . Using a rocking platform with controllable rocking conditions, the results of the present study reveal quantitative relations between hMSC aggregation kinetics and hydrodynamics, and demonstrate the potential of the rocking platform for large scale production of hMSC aggregates.…”
Section: Introductionmentioning
confidence: 64%
“…The application of this novel technology highlighted the need for further standard in-culture conditions aimed at stabilizing MSC phenotype. These include medium flow rate, sheer tension[49] and cell-microcarrier interactions[50]. …”
Section: Methods For Sorting Expansion and Storage: Application Of Gmpmentioning
confidence: 99%